Developmental dynamic interplay between executive functions and psychotic risk. Issue 2 (3rd April 2021) - Poletti, Michele; Gebhardt, Eva; Raballo, Andrea
Abstract: According to the neurodevelopmental hypothesis of schizophrenia, the premorbid stages of nonaffective psychosis are characterized by early phenotypic manifestations of neurobiological vulnerability, whose developmental trends are accurately characterized for IQ, language, and motor abilities. More elusive is the developmental relationship between psychotic risk and executive functions. Few longitudinal studies are available on this relationship, suggesting a developmental lag for executive functions in subjects that will develop psychosis in young adulthood. In this brief commentary we underline specific developmental characteristics of psychotic manifestations that should be considered by further studies, which are aimed at grasping the developmental relationship between psychotic risk and neurocognitive features. Psychosis is an end-stage phenomenon that represents the long-term outcome of a prolonged psychopathological construction. By designing studies addressing developmentally-sensitive risk phenotypes for psychosis, it will be possible to understand how executive functions (among other neurocognitive features) might impact the risk of developing psychosis.